Impact of Pediatric COVID-19 on Family Health-Related Quality of Life: A Qualitative Study from Latvia - Inese Stars; Liene Smane; Zanda Pucuka; Ieva Roge; Jana Pavare (SAGE Publishing, 2021)
Information on family health-related quality of life (FHRQoL) among families of children with the coronavirus disease 2019 (COVID-19) is limited. This qualitative study explores the impact of pediatric COVID-19 on FHRQoL from the parents' perspective. Semi-structured interviews were conducted with parents (n = 20) whose children had tested positive for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Inductive thematic analysis revealed the following 10 themes that represented parents' perception of FHRQoL while taking care of a child with COVID-19: pediatric COVID-19 as a disease with many unknowns; emotional saturation; internal family relationships in the context of "a new experience"; routine household activities and daily regimen while family is in lockdown; plenty of free time; a wide social support network; social stigma associated with COVID-19; different options for work; savings and debts; challenges with family housing and transport availability. Our results show that parents experience multiple effects of pediatric COVID-19 with regard to FHRQoL.